Prevalence of overweight and metabolic syndrome, and associated sociodemographic factors among adult Ecuadorian populations: the ENSANUT-ECU study - Pérez-Galarza, J. (J Endocrinol Invest, 2020)
BACKGROUND: Obesity and metabolic syndrome (MetS) are key risk factors for type 2 diabetes and cardiovascular disease. Little information exists on the prevalence of obesity and MetS in Latin America and specifically in Ecuador. We aimed to estimate the prevalence of overweight, obesity, and MetS among adults in Ecuador. METHODS: We analyzed data from a nation-wide population-based survey in Ecuador (ENSANUT-ECU) among 10,318 participants (3684 men, 6634 women; age range: 18–59 years) conducted in 2012. Data related to residential location (urban versus rural), altitude (< 500, 500–1500 or > 1500 m above sea level (MASL)), region (highland, coast, amazon, or Galápagos), and socioeconomic status were collected. BMI, waist circumference, blood lipids, glucose, and blood pressure were measured by trained fieldworkers following standardized procedures. RESULTS: The age-standardized prevalence of overweight was 39.5%; 22.3% was obese; and 31.2% had MetS. The prevalence of obesity, low HDL-cholesterol, and abdominal obesity were higher in women than in men, whereas men had a higher prevalence of hypertension (p < 0.05). Sex differences were not observed regarding the prevalence of combined MetS. Prevalence of both obesity and MetS was higher in urban areas, at low altitude regions (coast and Galapagos), and at high socioeconomic status (all p < 0.05). CONCLUSIONS: Prevalence of obesity and MetS in Ecuador are high. There are important demographic differences in the prevalence of MetS between Ecuadorian subpopulations that requires targeted research and prevention efforts, to hold and reduce the current public health problem of metabolic disorders. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s40618-020-01267-9) contains supplementary material, which is available to authorized users.